2012
DOI: 10.1186/2045-709x-20-35
|View full text |Cite
|
Sign up to set email alerts
|

The United States Chiropractic Workforce: An alternative or complement to primary care?

Abstract: BackgroundIn the United States (US) a shortage of primary care physicians has become evident. Other health care providers such as chiropractors might help address some of the nation’s primary care needs simply by being located in areas of lesser primary care resources. Therefore, the purpose of this study was to examine the distribution of the chiropractic workforce across the country and compare it to that of primary care physicians.MethodsWe used nationally representative data to estimate the per 100,000 cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…We found evidence to support previous findings that a higher supply of chiropractic care is correlated with PCP supply, 8 suggesting the 2 services are located in similar areas. In this study, however, we found stronger associations between the 2 services (potentially because we removed inactive providers).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We found evidence to support previous findings that a higher supply of chiropractic care is correlated with PCP supply, 8 suggesting the 2 services are located in similar areas. In this study, however, we found stronger associations between the 2 services (potentially because we removed inactive providers).…”
Section: Discussionsupporting
confidence: 88%
“…This finding is not surprising considering the chiropractic profession began in the Midwest (specifically in Davenport, Iowa, which had the highest supply of chiropractors of all HRRs). 8,26,27 Given that the supply of physicians in general exhibits a different pattern, 28 it may raise questions about the role of chiropractic care in improving access to care (particularly in rural locales). Previous studies have examined the potential role of chiropractic care in improving access to care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Commonly covered services include evaluation and management services, physical therapy modalities, radiographs, and some laboratory services 2 . Davis et al 3 estimated that there were 74,623 licensed DCs in the United States in 2006; and in that year, chiropractic physicians provided 18.6 million clinical services under Medicare Part B at a cost of $420 million 4 . Overall spending for chiropractic care in the United States totaled more than $5.9 billion in 2006 5 …”
Section: Introductionmentioning
confidence: 99%